The effects of age and sex on reference intervals for cobalamin, homocysteine, and serum and urinary methylmalonic acid in healthy adult dogs - Anna‐Lena Proksch; Sophia Schaefer; Vanessa Dreller; Judith Langenstein; Ralph Fingerhut; Natali Bauer; Andreas Moritz (Journal of Veterinary Internal Medicine)
Abstract Background In dogs, data on reference intervals (RIs) for cobalamin, markers of metabolism (markersB12met), age and sex effects are limited. Hypothesis/Objectives Establish RI for serum cobalamin, homocysteine, and methylmalonic acid (sMMA) concentrations, urinary methylmalonic acid‐to‐creatinine ratio (uMMA:crea), and determine effects of sex and age. Methods Prospective study using healthy dogs (1‐10 years). Cobalamin and markersB12met were determined using chemiluminescence immunoassay (cobalamin) and liquid chromatography/tandem mass spectrometry (homocysteine, sMMA, uMMA:crea). In dogs with outlying data, changes in health, markersB12met, and onset of gastrointestinal signs were reevaluated after 9‐15 months. Results Twelve of 120 healthy dogs had abnormal uMMA:crea ratios. No other cobalamin analyte outliers were found. Outlying data re‐examination (odRE) was performed in 10/12 dogs. Chronic gastrointestinal signs occurred in 64% of odRE‐dogs, whereas 36% remained healthy. In total, 112 dogs (67 females, 45 males; median ages, 3.5 and 3.75 years, respectively) were included in RI analyses. Reference intervals were 178.5‐851 pmol/L (cobalamin), 5.8‐29.0 μmol/L (homocysteine), 45.3‐159.5 μg/L (sMMA), and ≤22.4 mg/g (uMMA:crea). Only age affected cobalamin concentrations (significant decrease). Compared by sex and neuter status, intact male dogs had significantly higher uMMA:crea ratios (median, 13.5; range, 1.9‐83.6 mg/g) than the other groups (median, 2.5; range, 0.7‐9.7 mg/g; P < .0001). Sex‐specific RI were ≤58.9 mg/g (intact male) vs ≤5.2 mg/g (females and neutered males). Conclusion and Clinical Importance Intact male dogs had significantly higher uMMA:crea ratios than the other groups. Thus, sex‐specific RI are recommended for uMMA:crea. Because of the wide distribution of uMMA:crea ratios, careful interpretation in intact male dogs is advised.